2011
DOI: 10.1186/1472-6882-11-120
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salvia Miltiorrhiza ethanol extract as an anti-osteoporotic agent

Abstract: BackgroundSalvia miltiorrhiza (SM) has long been used as a traditional oriental medicine for cardiovascular disease. Accumulating evidence also indicates that SM has anti-osteoporotic effects. This study was conducted to examine the SM-induced anti-osteoporotic effect and its possible mechanisms with various doses of SM.MethodsWe studied Sprague-Dawley female rats aged 12 weeks, divided into six groups: sham-operated control (SHAM), OVX rats supplemented with SM (1, 3, 10 and 30 mg/kg) orally for 8 weeks. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
3
19
0
2
Order By: Relevance
“…Cui et al found that Salvia miltiorrhiza prevented OVX-induced bone loss probably due to its anti-oxidative stress and partly via modulation of osteoclast maturation and number, because it decreased the osteoclast activation marker TRAP-5b and oxidative stress parameters malondialdehyde (MDA) and NO induced by OVX (80). Individual compound tanshinone also prevented a decrease in trabecular bone volume and trabecular number and an increase in osteoclast surface in vertebra, and partially prevented a decrease in trabecular bone volume and trabecular number in the tibia (81).…”
Section: In Vivo Preclinical Datamentioning
confidence: 99%
“…Cui et al found that Salvia miltiorrhiza prevented OVX-induced bone loss probably due to its anti-oxidative stress and partly via modulation of osteoclast maturation and number, because it decreased the osteoclast activation marker TRAP-5b and oxidative stress parameters malondialdehyde (MDA) and NO induced by OVX (80). Individual compound tanshinone also prevented a decrease in trabecular bone volume and trabecular number and an increase in osteoclast surface in vertebra, and partially prevented a decrease in trabecular bone volume and trabecular number in the tibia (81).…”
Section: In Vivo Preclinical Datamentioning
confidence: 99%
“…Increased bone weight is considered a good indicator of anti-osteoporotic activities (77,78), despite the fact that changes in bone weight are not an important marker for evaluating anti-osteoporotic agents, with the exception of ash bone weight (79). For an osteoporosis-related OVX model, serum bALP content and osteocalcin levels are typically accepted as bone turnover markers (80)(81)(82), and BMD is used as a major determinant of osteoporosis (83)(84)(85). As microscopic observation of bone can provide good evidence regarding bone morphology (35,37,38,86), trabecular and cortical bone is significantly changed in osteoporotic animals.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize suffering, rats were operated under anesthesia by a mixture of ketamine (35 mg/kg) and xylazine (10 mg/kg) administrated intraperitoneally. Experimental rats were either ovariectomized (OVX) or sham operated (Sham) according to the protocol of Cui et al 15 and allocated to one of the eight groups (n = 10 in each group) as follows: Sham (group 1), OVX (group 2), MK-7-treated OVX (groups 3-5 at doses of 2, 4, and 8 lg/day, respectively), and CGJ-treated OVX (groups 6-8 at doses of 0.063, 0.125, and 0.250 g/day, referenced to the same MK-7 levels as 2, 4, and 8 lg/day, respectively). After a 7-day healing period, rats in the MK-7-and CGJ-treated OVX groups were orally administered serial doses of MK-7 or CGJ suspensions once daily for 8 weeks, while Sham and OVX groups were orally treated with volume-matched vehicles before sampling.…”
Section: Animalsmentioning
confidence: 99%
“…The scan length was 5 cm, the scan width 2 cm, and the scan speed was 10 mm/s with a resolution of 0.2 · 0.2 mm. 15,17 Bone histomorphometry Left tibiae were decalcified in a solution of 5% formic acid (in distilled water) for 1 week and then dehydrated with methanol and embedded in paraffin. Paraffin sections were deparaffinized and sectioned at 4 lm with an AO Autocut/ Jung 1150 microtome.…”
Section: Bone Mass Measurements By Dual-energy X-ray Absorptiometrymentioning
confidence: 99%
See 1 more Smart Citation